Two Tracks of Thought: A Structural Model of the Test for Creative Thinking-Drawing Production (TCT-DP). Issue 2 (3rd April 2017) - Nogueira, Sara Ibérico; Almeida, Leonor S.; Lima, Tiago Souza
Abstract : The Test for Creative Thinking-Drawing Production (TCT-DP, Urban & Jellen, 1986) is one of the most used instruments for the assessment of creative potential. Few studies exist regarding its factorial structure, and all of them were limited to using an exploratory approach. The aim of this research was to assess the factorial structure of the TCT-DP (Form A) for undergraduate and postgraduate Portuguese students. Two studies were performed, where Study 1 (967 participants) consisted of an exploratory factor analysis (EFA) that yielded a 2-factor solution and Study 2 (920 participants) consisted of a confirmatory factor analysis (CFA) used to test the fit and compare the suitability of the 2 factorial solutions with alternative models. The 2-factor model exhibited good and acceptable indices of fit. The factors represented Innovativeness and Adaptiveness. This model was called Two Tracks of Thought (TTT). Its structure suggests the importance of both non-conventional and conventional thinking for the creative process.